Hypolipidemic effect of Arthrospira (Spirulina) maxima Supplementation and a Systematic Physical Exercise Program in Overweight and Obese Men: A Double-Blind, Randomized, and Crossover Controlled Trial - Hernandez Lepe, Marco Antonio (2019)
Low-fat diets, lipid-modifying nutraceuticals and a higher level of physical activity are often recommended to reduce dyslipidemia. A double-blind, randomized, crossover, controlled trial was designed to evaluate the independent and synergistic effects of Arthrospira (Spirulina) maxima supplementation (4.5 g·day−1) with or without performing a physical exercise program (PEP: aerobic exercise (3 days·week−1) + high-intensity interval training (2 days·week−1)) on blood lipids and BMI of 52 sedentary men with excess body weight. During six weeks, all participants were assigned to four intervention treatments (Spirulina maxima with PEP (SE), placebo with PEP (Ex), Spirulina maxima without PEP (Sm), placebo without PEP (C; control)) and plasma lipids were evaluated spectrophotometrically pre- vs. post intervention in stratified subgroups (overweight, obese and dyslipidemic subjects). Pre/post comparisons showed significant reductions in all plasma lipids in the SE group, particularly in those with dyslipidemia (p ≤ 0.043). Comparing the final vs. the initial values, BMI, total cholesterol, triglycerides and low-density lipoprotein cholesterol were decreased. High-density lipoprotein cholesterol increased in all treatment groups compared to C. Changes were observed mostly in SE interventions, particularly in dyslipidemic subjects (p < 0.05). Spirulina maxima supplementation enhances the hypolipidemic effect of a systematic PEP in men with excess body weight and dyslipidemia.